Xietu Hemu Prescription Improves Metabolic Dysfunction-Associated Steatotic Liver Disease: A Real-World Cohort Study - Xiang LL; Cao YT; Wang XX; Wang GX; Zhang YJ; Li RH; Qi F; Huai JX; Sun J; He XJ; Zhou XQ (Journal of Multidisciplinary Healthcare, 2025)
Liu-lan Xiang,1,2,* Yu-tian Cao,1,2,* Xiao-xiao Wang,3,* Gao-xiang Wang,1,* Yu-juan Zhang,4 Rui-han Li,1,2 Fang Qi,5 Jia-xuan Huai,1,2 Jing Sun,1,2 Xiao-jin He,3 Xi-qiao Zhou1 1Department of Endocrinology, Affiliated Hospital of Nanjing University of Chinese Medicine, Jiangsu Province Hospital of Chinese Medicine, Nanjing, People’s Republic of China; 2The First Clinical Medical College of Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China; 3Affiliated Hospital of Nanjing University of Chinese Medicine, Jiangsu Province Hospital of Chinese Medicine, Nanjing, People’s Republic of China; 4Department of Endocrinology, Seventh People’s Hospital of Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 5Department of Geriatrics, Panjin Liao-Oil Field Gem Flower Hospital, Liaoning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xi-qiao Zhou, Email zhouxiqiao@njucm.edu.cn Xiao-jin He, Email xomaestro@163.comPurpose: This study aims to evaluate the efficacy of the Xietu Hemu prescription (XHP) in improving metabolic dysfunction-associated steatotic liver disease (MASLD) through a Real World Study approach.Methods: This was a single-center, prospective, real-world cohort study of 262 patients with MASLD who met the inclusion and exclusion criteria from November 2021 to November 2023 at Jiangsu Provincial Hospital of Traditional Chinese Medicine. The exposure of this study was who took the XHP. We assessed the efficacy of the XHP on MASLD by comparing FibroScan parameters, body composition indicators, and liver serological indicators. The XHP was then evaluated for MASLD by inverse probability of treatment weighting (IPTW) as well as log-binomial analysis.Results: We ended up collecting the exposure cohort (n=163) and the referent cohort (n=99). Patients were categorized into an exposure cohort (n=163, XHP + basic treatment) subdivided by treatment duration: 4 weeks (n=28), 8 weeks (n=60), 12 weeks (n=51), and ≥ 16 weeks (n=24), and a referent cohort (n=99, basic treatment alone). The results showed significant improvements in Liver stiffness measurement (LSM), controlled attenuation parameter (CAP), body mass index (BMI), waist-to-hip ratio (WHR), visceral fat area (VFA), the fatty liver index (FLI), and FibroScan-AST (FAST) in the exposure cohort after treatment compared to before treatment. After controlling confounding by IPTW, log-binomial analysis revealed that XHP administration was significantly more effective for MASLD in the exposure cohort than in the referent cohort (weighted risk ratio=2.99, 95% CI=1.86 to 4.89, p< 0.001). Subgroup analyses revealed a significantly greater efficacy of the XHP in the exposure cohort compared to the MASLD referent cohort, across various durations and dosages of XHP and varying degrees of hepatic steatosis and fibrosis. No serious adverse events occurred; occasional mild gastrointestinal reactions were self-limiting.Conclusion: The results of our study suggest that XHP has a significant treatment effect on MASLD, which hopes to complement the current lack of treatment for MASLD.Keywords: MASLD, Xietu Hemu prescription, efficacy, real-world study, Chinese medicine